2018
DOI: 10.1021/acs.estlett.8b00386
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Silicate Crystal Structure Impacts Reactivity with CO2 and Precipitate Chemistry

Abstract: The reaction of CO 2(aq) with calcium silicates creates precipitates that can impact fluid flow in subsurface applications such as geologic CO 2 storage and geothermal energy. These reactions nominally produce calcium carbonate (CaCO 3 ) and amorphous silica (SiO x ). Here we report evidence that the crystal structure of the parent silicate determines the way in which it reacts with CO 2 and the resulting structures of the reaction products. Batch experiments were performed using two polymorphs of a model calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Experimental results published recently by several independent research groups including ours suggests that the coprecipitation of crystalline calcium silicate hydrates (CCSH) phases and carbonates is possible using pseudowollastonite, a polymorph of CaSiO 3 , which is more reactive than the alternate polymorph, wollastonite , The formation of CCSH phases, represented in eqs and , may occur in parallel or sequence with the carbonation reactions that proceed via eq , but typically, one class of precipitate predominates, depending on reaction conditions. XRF maps, such as the one used in the abstract graphic, reveal that CCSHs tend to precipitate along solid interfaces such as sand grains, whereas carbonates tend to precipitate indiscriminately throughout pore bodies .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Experimental results published recently by several independent research groups including ours suggests that the coprecipitation of crystalline calcium silicate hydrates (CCSH) phases and carbonates is possible using pseudowollastonite, a polymorph of CaSiO 3 , which is more reactive than the alternate polymorph, wollastonite , The formation of CCSH phases, represented in eqs and , may occur in parallel or sequence with the carbonation reactions that proceed via eq , but typically, one class of precipitate predominates, depending on reaction conditions. XRF maps, such as the one used in the abstract graphic, reveal that CCSHs tend to precipitate along solid interfaces such as sand grains, whereas carbonates tend to precipitate indiscriminately throughout pore bodies .…”
Section: Resultsmentioning
confidence: 96%
“…Several recent studies have reported that the carbonation of a model calcium silicate at elevated temperatures results in the formation of carbonate in addition to crystalline calcium silicate hydrate (CCSH) phases. 10,11 These CCSH phases are mixed, consisting of a mineral species such as tobermorites via…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In chain-silicate minerals, preferential leaching of the cation allows the precipitation of solid carbonates in the presence of CO 2(aq) and leaves a relatively unreactive porous silica network that condenses over time . Our group recently reported that some mineral silicates can react with CO 2(aq) to generate noncarbonate products . Specifically, a ring-structured calcium silicate, pseudowollastonite (CaSiO 3 ) was shown to generate crystalline calcium silicate hydrates (CCSHs) in addition to Ca-carbonate when pH was increased at elevated temperature (150 °C) and moderate CO 2 concentration (0.18 M).…”
Section: Introductionmentioning
confidence: 99%
“…These objectives were studied first via a series of sand column experiments that simulate porous media, in which pseudowollastonite was injected and then reacted with CO 2(aq) . Pseudowollastonite was selected based on our previous study that found it can generate a variety of carbonate and CCSHs, based on aqueous conditions . The reacted columns were then characterized via synchrotron-based X-ray diffraction and X-ray fluorescence mapping as well as with electron microscope analyses which, together, allowed for spatial mapping of product phases under various conditions over time.…”
Section: Introductionmentioning
confidence: 99%